Exegesis in the Making: Postcolonialism and New Testament Studies - Runesson, Anna (Biblical Interpretation Ser., 2010)
Known for its fresh approaches as well as for its complex theoretical foundations, postcolonialstudies is one of the most dynamic contributions to the field of biblical studies today. The presentbook is a pedagogically structured introduction to this emerging field for both scholar and student.